Impact of grape variety, berry maturity and size on the extractability of skin polyphenols during model wine‐like maceration experiments. (15th December 2020) - Abi‐Habib, Elissa; Poncet‐Legrand, Céline; Roi, Stéphanie; Carrillo, Stéphanie; Doco, Thierry; Vernhet, Aude
Abstract: BACKGROUND: Skin cell walls modulate anthocyanin and tannin extraction from grape skins. However, relationships between the composition of alcohol‐insoluble cell wall solids (AIS) and extraction are still unclear. Our objectives were to characterize the impact of variety, berry size and ripeness on skin AIS composition (polysaccharides, proteins) and polyphenol extraction during maceration. RESULTS: Grape skin composition and its impact on polyphenol extraction was compared for two varieties – Carignan and Grenache – with skins of berries sorted according to their size and density. Extractions were performed under model wine‐like maceration conditions. Fresh skins had similar content of polymeric tannins, but strongly differed in their anthocyanin content (higher in Carignan and in the ripest berries) and composition (higher proportions in coumaroylated anthocyanins in Carignan). Anthocyanin extraction was proportionally much higher in Grenache, which was not just related to the Carignan's higher levels in coumaroylated anthocyanins. Chemical reactions decreased anthocyanin concentrations in solution for both varieties. Tannin extraction for Grenache was slightly higher and faster than for Carignan. Skin AISs differed slightly between the two varieties in their carbohydrate composition and protein content, but not between modalities. Polyphenol analyses in the precipitates evidenced at the end of the maceration and in residual skins highlighted differences between the two varieties and between berries with different ripeness. CONCLUSION: Structural information on the cell wall network and on its changes during maceration, along with a better understanding of the chemical reactions of anthocyanins and tannins, is needed to better relate grape and wine polyphenol composition. © 2020 Society of Chemical Industry